A systematic review of adverse drug events associated with administration of common asthma medications in children. - James S Leung; David W Johnson; Arissa J Sperou; Jennifer Crotts; Erik Saude; Lisa Hartling; Antonia Stang (PLoS ONE)
Objective To systematically review the literature and determine frequencies of adverse drug events (ADE) associated with pediatric asthma medications. Methods Following PRISMA guidelines, we systematically searched six bibliographic databases between January 1991 and January 2017. Study eligibility, data extraction and quality assessment were independently completed and verified by two reviewers. We included randomized control trials (RCT), case-control, cohort, or quasi-experimental studies where the primary objective was identifying ADE in children 1 month- 18 years old exposed to commercial asthma medications. The primary outcome was ADE frequency. Findings Our search identified 14,540 citations. 46 studies were included: 24 RCT, 15 cohort, 4 RCT pooled analyses, 1 case-control, 1 open-label trial and 1 quasi-experimental study. Studies examined the following drug classes: inhaled corticosteroids (ICS) (n = 24), short-acting beta-agonists (n = 10), long-acting beta-agonists (LABA) (n = 3), ICS + LABA (n = 3), Leukotriene Receptor Antagonists (n = 3) and others (n = 3). 29 studies occurred in North America, and 29 were industry funded. We report a detailed index of 406 ADE descriptions and frequencies organized by drug class. The majority of data focuses on ICS, with 174 ADE affecting 13 organ systems including adrenal and growth suppression. We observed serious ADE, although they were rare, with frequency ranging between 0.9-6% per drug. There were no confirmed deaths, except for 13 potential deaths in a LABA study including combined adult and pediatric participants. We identified substantial methodological concerns, particularly with identifying ADE and determining severity. No studies utilized available standardized causality, severity or preventability assessments. Conclusion The majority of studies focus on ICS, with adrenal and growth suppression described. Serious ADE are relatively uncommon, with no confirmed pediatric deaths. We identify substantial methodological concerns, highlighting need for standardization with future research examining pediatric asthma medication safety.